Some like it hot - Wilder, Billy, 1906-2002; Diamond, I. A. L.; Monroe, Marilyn, 1926-1962; Curtis, Tony, 1925-2010; Lemmon, Jack; Brown, Joe E., 1892-1973, (Joe Evan); Raft, George; O'Brien, Pat, 1899-1983 (Santa Monica, Calif. : MGM Home Entertainment, 2001)
Two unemployed musicians accidentally witness the St. Valentine's Day Massacre and flee to Miami disguised as female musicians in an all-girl band.
Originally released as motion picture by United Artists Corp. in 1959.
Ashton Productions, Inc. presents a Mirisch Company picture ; produced and directed by Billy Wilder ; screenplay by Billy Wilder and I.A.L. Diamond, suggested by a story by R. Thoeren and M. Logan ; director of photography, Charles Lang, Jr. ; art director, Ted Haworth ; film editor, Arthur P. Schmidt ; background score, Adolph Deutsch ; costume designer, Orry-Kelly.
Marilyn Monroe, Tony Curtis, Jack Lemmon, Joe E. Brown, George Raft, Pat O'Brien.
Keywords: Female impersonators -- Drama; Musicians -- Drama; Gangsters -- Drama; Feature films